Evolutionary psychology and violence : a primer for policymakers and public policy advocates - Bloom, Richard W., 1944-; Dess, Nancy Kimberly (Psychological dimensions to war and peace., 2003)
Each chapter in this volume poses a public policy issue related to violence, describes aspects of evolutionary psychology that are relative, and then posits public policy recommendations based on this psychological model. Topics covered also include psychopathy, despotism, and suicide bombings. This volume is designed as an accessible way for policymakers outside of academia to learn about new theoretical developments.